LOGICAL-STATIC PLANNING COMPLEX TECHNICAL OBJECTS OPERATIONS AND FUNCTIONING MODES - Pavlov, Alexander N.; Pavlov, Dmitry A.; Ivanyu, Anna Yu.; Zakharov, Valerii V.; Barashenkov, Nikolay A. (Journal of Applied Engineering Science, 2025)
A definition of operating mode of complex technical object (CTO) concept is introduced. A logical-static interpretation of CTO operating modes is given. A formal grammar of transformations of logical functions for compatibility (incompatibility) of operations in constraints of a static planning model is presented. Transformation rules are introduced for specific cases. An algorithm for formalizing logical multi-mode structures of CTO functioning in static planning terms of operation flows and modes is developed. Results of computational experiments are presented.
Keywords: modes of functioning, parametric genome of structure, structural and functional survivability, motion control system, small spacecraft, onboard control complex.